Philippines 2000 for realn ; Made in Japan ; Music from the heart [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Talks about the State of the Nation Address of President Ramos on economic campaign to propel the Philippines to NIC status by the year 2000. The plight of Japinos on thier rights unders Japanese aid Philippine laws. Pianist-composer Jim Chapell was interviewed by Probe Team on the kind of music he composes.